COVID-19 AND ECONOMIC POLICY OPTIONS: WHAT SHOULD THE GOVERNMENT DO? - Faisal, Muhammad; Nirmala, Muthia Prima (Jurnal Inovasi Ekonomi, 2020)
The Coronavirus disease (COVID-19) continues to grow rapidly from day to day in every part of the world and it is uncertain when this pandemic will decline. The world economy is experiencing a hard blow from COVID-19 both directly and indirectly, which is reflected in the many industrial sectors of many countries that have struggled to recover. This paper tries to map the economic impacts that are generally experienced by countries in the world affected by the pandemic, then formulates some recommendations related to the government's response in dealing with the COVID-19 pandemic as an option in effort to minimize wider economic impacts. This paper can contribute to policymakers in every government in the world and provide action options in dealing with the shock of the COVID-19 pandemic.